Defense protocol - Andrews, Brian, 1973-; Wilson, Jeff, 1963-; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel ;, 2024)
Every word a president utters is weighed and examined, but none more so than when he is talking about Taiwan. That's why it's shocking that President Jack Ryan seems to imply that the US has no appetite for a war to protect Taiwan from the communist Chinese on the mainland. President Ryan is determined to protect the independence of the island nation, but he is determined that one slip of the tongue should not cost thousands of young soldiers, sailors and Marines their lives. Jack Ryan returns in a blockbuster novel of action, thrills and intrigue in the world created by master storyteller Tom Clancy.